Combined islet and kidney xenotransplantation for diabetic nephropathy: an update in ongoing research for a clinically relevant application of porcine islet transplantation - Daniel L. Eisenson; Hayato Iwase; Weili Chen; Yu Hisadome; Wanxing Cui; Michelle R. Santillan; Alexander C. Schulick; Du Gu; Amanda Maxwell; Kristy Koenig; Zhaoli Sun; Daniel Warren; et al. (Frontiers in Immunology, 2024)
Combined islet and kidney xenotransplantation for the treatment of diabetic nephropathy represents a compelling and increasingly relevant therapeutic possibility for an ever-growing number of patients who would benefit from both durable renal replacement and cure of the underlying cause of their renal insufficiency: diabetes. Here we briefly review immune barriers to islet transplantation, highlight preclinical progress in the field, and summarize our experience with combined islet and kidney xenotransplantation, including both challenges with islet-kidney composite grafts as well as our recent success with sequential kidney followed by islet xenotransplantation in a pig-to-baboon model.